The assessment of occupational safety and health in Turkey by applying a decision-making method; MULTIMOORA. Issue 6 (2nd July 2020) - Dizdar, Ercüment Neşet; Ünver, Muharrem
Abstract: This article presents an application of multi-objective decision-making approach by using multi-objective optimization plus the full multiplicative form (MULTIMOORA) method on the assessment procedure of occupational safety and health based on the counts of occupational accidents and diseases. The method determines the ranks of the years which are decision-making units and designed as time-series analysis. The aim is to determine the occupational safety and health status in Turkey based on the recorded data. The data used in this study indicate an increasing number of worker and occupational safety experts versus a fluctuating trend of the case count of the occupational accidents and diseases. The final ranks obtained from MULTIMOORA show that the last three years assessed in this study have a higher efficiency compared to the previous five years. MULTIMOORA is a simple and quite easy to use method with less computational time.